ANALISIS KESALAHAN PENGGUNAAN KATA DALAM KARANGAN NARASI SISWA KELAS V MI TARBIYATUL ISLAMIYAH BUMIREJO KEPOHBARU BOJONEGORO - Bisarul Ihsan; Tisnis Nur Cahaya Putri; Rina Sari (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2018)
This study aims to 1) describe the word formation errors in the narrative essays of class V MI Tarbiyatul Islamiyah Bumirejo, 2) describe the conceptual misconceptions in the narrative essays of class V MI Tarbiyatul Islamiyah Bumirejo, and 3) describe the use of non-standard words in narrative essays Grade V student at MI Tarbiyatul Islamiyah Bumirejo. The method of this research is qualitative descriptive research with the subject of research on class V students of MI Tarbiyatul Islamiyah in the subdistrict of Kepohbaru, Bojonegoro Regency. The results of this study are (1) word formation errors include prefix removal errors, word repetition errors, absence of leaching, misuse of prefixes, and absence of suffixes, (2) misconceptions of meaning include lack of mastery of someone's words when making narrative essays, (3) errors in the use of non-standard words include errors in the use of official spelling in written forms.